Neuroprotection by dimethyloxalylglycine following permanent and transient focal cerebral ischemia in rats. - Nagel, S; Papadakis, M; Chen, R; Hoyte, L; Brooks, K; Gallichan, D; Sibson, N; Pugh, C; Buchan, A (2011)
Dimethyloxalylglycine (DMOG) is an inhibitor of prolyl-4-hydroxylase domain (PHD) enzymes that regulate the stability of hypoxia-inducible factor (HIF). We investigated the effect of DMOG on the outcome after permanent and transient middle cerebral artery occlusion (p/tMCAO) in the rat. Before and after pMCAO, rats were treated with 40 mg/kg, 200 mg/kg DMOG, or vehicle, and with 40 mg/kg or vehicle after tMCAO. Serial magnetic resonance imaging (MRI) was performed to assess infarct evolution and regional cerebral blood flow (rCBF). Both doses significantly reduced infarct volumes, but only 40 mg/kg improved the behavior after 24 hours of pMCAO. Animals receiving 40 mg/kg were more likely to maintain rCBF values above 30% from the contralateral hemisphere within 24 hours of pMCAO. DMOG after tMCAO significantly reduced the infarct volumes and improved behavior at 24 hours and 8 days and also improved the rCBF after 24 hours. A consistent and significant upregulation of both mRNA and protein levels of vascular endothelial growth factor (VEGF) and endothelial nitric oxide synthase (eNOS) was associated with the observed neuroprotection, although this was not consistently related to HIF-1α levels at 24 hours and 8 days. Thus, DMOG afforded neuroprotection both at 24 hours after pMCAO and at 24 hours and 8 days after tMCAO. This effect was associated with an increase of VEGF and eNOS and was mediated by improved rCBF after DMOG treatment.